Balancing waiting times in sequential servers appointment system using distributionally robust optimization - Goh, You Hui (Nanyang Technological University, 2023)
This thesis studies an appointment scheduling problem with multiple sequential servers from a distributionally robust optimization (DRO) perspective. Using a moment-based ambiguity set along with conic optimization, our DRO models can capture the correlation between the random service times. A cost minimization model assuming linear waiting cost is first used to formulate a DRO model to find an optimal appointment schedule that minimizes the total systems' cost. We find that the schedule obtained can lead to an imbalanced waiting time across the servers, concentrating on the downstream servers. To ensure a balanced waiting time across the sequential servers, two approaches are studied.